PENGEMBANGAN URBAN FARMING MENUJU KETAHANAN PANGAN KELUARGA - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
In Mergosono Village, the program for using terraces to grow crops was carried out more than 5 years ago, through an “urban farming” program led by PKK women. There were more than 50 mothers who were involved in this activity. Through urban farming, each house is recommended to plant more than 10 potted plants, with various kinds of plants, such as: chilies, tomatoes, cabbage, eggplant, pok cay, mustard greens, and flowers. At first this activity only aimed to maintain the beauty of the village, so that it remains beautiful, but gradually it can be used to meet daily food needs, especially vegetables and "empon-empon". Even though this activity has been going on for more than 5 years, there are still many obstacles that they face, including: 1) PKK women are still not able to make special planting models for limited land, be it hydroponics or verticulture, therefore only polybag or pot models; 2) it is difficult to make a fertile planting medium, it seems that there are some plants that grow less healthy; 2) have not been able to create their own nurseries and have difficulty moving plants from the nursery box to pots or polybags; 3) have not been able to make environmentally friendly fertilizers (organic or compost); 4) have not mastered how to fertilize and when to fertilize properly; 5) do not understand good plant care techniques, do not know plant pests, and eradicate them, how to handle weeds). Therefore, assistance is needed to solve these problems in the form of technology transfer through training activities, mentoring, demonstration plots or direct practice.